PENERAPAN MODEL COOPERATIVE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
This research wanted to identify whether the implementation of Cooperative Snowball Throwing could increase the achievements of the 4th grade students of MIN 42 Pidie. This research was a Classroom Action Research. The results described in qualitative data analyzing. It was found that the average scores of the students increased significantly in each cycle. Cycle I was 70.23, cycle II was 81,36 and cycle III was 87,27. Thus, the implementation of Cooperative Snowball Throwing could improve the students’ achievements in learning.